2015
DOI: 10.1177/1534508415616583
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Educators’ Perceptions of Their Skills Relative to Response to Intervention

Abstract: The Perceptions of RtI Skills Survey is a self-report measure that assesses educators’ perceptions of their data-based problem-solving skills—a critical element of many Response-to-Intervention (RtI) models. Confirmatory factor analysis (CFA) was used to evaluate the underlying factor structure of this tool. Educators from 68 (n = 2,397) and 60 (n = 1,961) schools in a southeastern state participated during the spring of 2008 and spring of 2010, respectively. Results supported a correlated three-factor model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Although Blum and Cheny (2009) | 653 implementation fidelity. Castillo et al (2016) found low to moderate correlations between the PRSS and implementation checklists at Tiers 1 and 2, though more work is clearly needed in this area.…”
Section: Implications For Research and Practicementioning
confidence: 92%
See 2 more Smart Citations
“…Although Blum and Cheny (2009) | 653 implementation fidelity. Castillo et al (2016) found low to moderate correlations between the PRSS and implementation checklists at Tiers 1 and 2, though more work is clearly needed in this area.…”
Section: Implications For Research and Practicementioning
confidence: 92%
“…Confirmatory factor analysis revealed five factors with adequate to high internal consistency: Specialized Behavior Supports and Practices (α = 0.86), Targeted Intervention Supports and Practices (α = 0.87), Schoolwide PBS Practices (α = 0.86), Individualized Curriculum Supports (α = 0.84), and Positive Classroom Supports and Practices (α = 0.82). Castillo et al (2010Castillo et al ( , 2012Castillo et al ( , 2016 created the Perception of RTI Skills Survey (PRSS) as an assessment for educators working in schools using a three-tiered system of intervention supports. The PRSS is a self-report tool of educators' problem-solving skills.…”
Section: Current Mtss Assessments Of Knowledge and Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of the role that confidence plays in DBDM is critical because of its influence on teacher use of data to inform instruction. Teachers’ perceived ability and confidence can directly relate to their data use (Castillo et al, 2016a). Indeed, several studies have shown that a lack of confidence significantly contributes to the use, or nonuse, of student data (Datnow & Hubbard, 2016; van Geel et al, 2017).…”
Section: Teacher Confidencementioning
confidence: 99%
“…PD also impacts teachers’ confidence (Coburn & Turner, 2011; Levy-Vered & Nasser-Abu Alhija, 2015). Castillo and colleagues conducted a series of studies examining the relation of PD and teacher confidence and perceptions and found that PD has a positive impact on teachers’ confidence when it comes to assessment practices and data use (Castillo et al, 2016a; Castillo et al, 2016b; Castillo et al, 2018). Gotch and McLean (2019) found that even though knowledge did not increase following PD, teachers’ confidence did.…”
Section: Pdmentioning
confidence: 99%